Hearing loss in patients with Morquio A syndrome: A scoping review - Diaz-Ordoñez, Lorena; Duque-Cordoba, Paola Andrea; Silva-Cuero, Katherine; Gutierrez-Medina, Juan David; Saldarriaga, Wilmar; Murgašová, Lenka; Magner, Martin; Candelo, Estephania; Pachajoa, Harry (Medicine, 2025)
BACKGROUND: Hearing impairment is a prevalent clinical feature in Morquio syndrome (mucopolysaccharidosis IVA or MPS IVA) patients, often presenting in diverse forms: conductive, sensorineural, or a combination known as mixed hearing loss. The mixed form entails a blend of both conductive and sensorineural elements, typically exhibiting a progressive trajectory. This scoping review aimed to comprehensively analyze available evidence pertaining to the pathophysiology, classification, epidemiology, and clinical management of hearing loss in individuals with MPS IVA. METHODS: Targeted literature was searched using MEDLINE, Literatura Latino-Americana e do Caribe em Ciências da Saúde, Web of Science, the Cochrane Library, Trip Medical Database, Embase, ScienceDirect, and Google Scholar, with a second search cycle to identify gray literature. A systematic search strategy using Medical Subject Headings keywords was implemented: "Hearing Disorders" OR "Hearing Loss" AND "Mucopolysaccharidosis IV" or "Hearing Disorders" OR "Hearing Loss" AND "Mucopolysaccharidosis IV." The identified bibliography was uploaded to COVIDENCE platform for information management. Articles were screened by 3 independent reviewers following the eligibility criteria. RESULTS: Twenty-seven articles met the inclusion criteria, spanning information from 568 patients across 16 different countries. None of the studies had complete epidemiological information. Only 2 studies provided sufficient data to address the pathophysiology, while 3 addressed management and treatment. Hearing loss was reported in 210 of 568 patients. A total of 19.2% of patients reported recurrent ear infections. None of the studies reported vertigo, tinnitus, or dizziness in the patients. Pure-tone audiometry was the primary test used to diagnose and monitor auditory impairment in patients with Morquio syndrome. CONCLUSIONS: Five hundred sixty-eight patients with MPS IVA were identified, of whom 210 (37%) developed hearing loss, the most common of which was moderate. Despite the lack of information on the diagnosis and management of hearing loss in Morquio syndrome, this study found that approximately one-third of participants exhibited some form of auditory impairment, with the majority of these cases being sensorineural in nature.
Keywords: mukopolysacharidóza IV; lidé; nedoslýchavost; Humans; Hearing Loss; Mucopolysaccharidosis IV